Golden Noir in literary adaptation: From Rubem Fonseca to the 'agosto' mini-series cliché - Bulhões, Marcelo Magalhães [UNESP] (Universidade Estadual de Londrina, 2017)
The purpose of this article is to evaluate the adaptation of 'Agosto' (August) - a novel by Rubem Fonseca - produced by TV Globo television. Such evaluation will try to assess the issue of audiovisual adaptation as an intersemiotic phenomenon, focusing on a genre whose history is an example of the dynamics of absorption, transformation and recreation that involves the relationships between movies and literature: the noir fiction.
Noir dourado da adaptação literária: De Rubem Fonseca ao clichê da minissérie agosto
Keywords: Cinema; Literary adaptation; Noir; Television